Performing Jane : A Cultural History of Jane Austen Fandom - Glosson, Sarah (Book collections on Project MUSE., 2020)
""Performing Jane" expands the history of fandom by exploring the ways in which early Jane Austen fandom prefigured many of the features we recognize in media fandom today. Because Jane Austen fandom has been predominantly driven by women and in celebration of the works of a woman, the project provides a much-needed counterbalance to the preponderance of studies devoted to male-centered fandoms. Glosson explores three modes of fannish engagement -- collecting, creating imitative works, and pilgrimage -- and follows them through the two hundred years since Austen's work was first published, up through the digital age of today. Because Jane Austen has beautifully bridged both literary and popular culture realms, she makes an excellent case study to understand the ways we draw distinctions between fandom and other forms of intensive engagement, and, more importantly, to understand how fluid those distinctions can be. From historical newspapers to troves of print and online fanfiction, from private scrapbooks to Tumblr pages, Performing Jane embraces a holistic view of Jane Austen fandom's long history, relying on archival research, literary and visual analyses, and ethnographic work. It demonstrates the ways that fan practices-today and in the past-are performative, providing fresh insight into fandom and challenging long-held assumptions"--